Role of chest x-ray in assessing severity of pneumonia in children aged 3 months to 59 months - Dr. Dipty L Jain; Dr. Shruti Mishra; Dr. Harshwardhan Jain; Dr. Mounica Reddy; Dr. Sanjay B Agrawal (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Pneumonia is the leading cause of death in children worldwide. Accurate assessment of severity and prognosis is important to decide management of pneumonia. The objective of present study is to study role of Chest X-ray in predicting severity of pneumonia in children. Material & Methods: A total of 307 children aged 3 months to 59 months diagnosed with Pneumonia & Severe pneumonia as per World Health Organization (WHO) criteria were included in study. Chest radiographs were reported by Pediatric Radiologist and findings classified as Normal, Primary End point consolidation, Other Infiltrates, Pleural effusion. Results were compared in sub-group i.e. Pneumonia & Severe Pneumonia. Result: Hypoxia, cyanosis, grunting and severe malnutrition were found to be poor predictors of radiographic pneumonia. Bilateral infiltrates (30%) & Primary end point consolidation on right side (17%) are independent determinant of severity of pneumonia. Bilateral consolidation and bilateral pleural effusion on chest X-ray are associated with poor outcome. Conclusion: Children with cyanosis, grunting, hypoxia & severe malnutrition should preferentially have chest Xray done since they are more likely to have consolidation, infiltrates or pleural effusion. Children with Bilateral infiltrates, Consolidation and Bilateral pleural effusion should preferably be admitted to pediatric intensive care unit for more aggressive monitoring and management, since they have poor outcome.